Reading quality level of controlled noise in a study room at Puncak Alam’s local university / Lokman Hakim Abdul Razak - Abdul Razak, Lokman Hakim (2022)
Reading skills can be enhanced and help build a better quality of focus by identify sound and the environment. While sound as a whole may not necessarily be unsettling, the excessive unpleasant sound turns to noise and can vitiate the ambiance of a room. It is therefore of paramount importance that the noise controlling factor of a room be considered and methods to mitigate the noise be implemented where necessary. A set of noise disturbance are made to identify how a person can endure and the quality of reading can be sustained in a controlled noise. Previous research has primarily relied on an impactful learning method in a study room need excellent noise level quality. Due to the poor quality of the study environment, frequent speech repetition can lead to a variety of emotional disorders in students. This study objective to determine the noise level of in a study room and evaluate the impact in reading performance.